Evaluation of person-centred care within the Stepstones transition program for adolescents with congenital heart disease – a document analysis - Åsa Burström; Markus Saarijärvi; Sandra Skogby; Anna Lena Brorsson; Ewa-Lena Bratt; Carina Sparud-Lundin (International Journal of Nursing Studies Advances)
Background: Transition programs are pivotal in ensuring successful transition to adulthood and transfer to adult care for adolescents with chronic conditions. Healthcare providers must therefore support adolescents in increasing their empowerment to gain active participation in health and care. The Stepstones transition program is based on a person-centred care approach and has been evaluated in a randomized controlled trial. However, the extent to which the person-centred care approach was implemented needs further exploration. Objective: To evaluate how a person-centred care approach was implemented based on a documentation analysis of the Stepstones transition program for adolescents with congenital heart disease. Design: A deductive qualitative design employing analysis of the documentation used in the Stepstones transition program. Setting(s): The documentation derives from the consultations in the two interventions centres in the Stepstones randomized controlled trial. The trial was conducted between 2017 and 2021. Data sources included in this study were: The adolescents’ written narratives, documentation of the person-centred conversations, and goalsetting in the transition plans. Participants: Documentation for adolescents with congenital heart disease, randomized to the intervention group (n = 59) at the two intervention centres was included. Methods: Directed content analysis was used to evaluate how person-centred care was described in the documentation. The analysis was based on the three cornerstones of person-centred care: initiating, establishing and safeguarding partnership, in this study between the adolescent and the transition coordinator during the transition program. The data were deductively sorted into aspects of relevance for person-centred care and adolescent health. For the written narratives an inductive analysis was thereafter undertaken. Results: A partnership between the transition coordinator and the adolescent was initiated through the adolescents’ written narrative and established using a psychosocial interview guide. This outlined a spectrum of aspects important to person-centred and adolescent-oriented approach, such as resources, risks/obstacles, and needs. The goalsetting process describes goals commonly agreed upon and how to accomplish them. A solid foundation of self-awareness regarding personal capacities and learning needs contributed to the development of knowledge, understanding, and fostered independence to various degrees. Conclusions: The Stepstones transition program for adolescents with congenital heart disease implemented several person-centred components, such as eliciting narratives, collaborative goal setting, and tailoring support needs. The documentation had limitations in fully reflecting the person-centred practices employed, highlighting opportunities for improvement in person-centred documentation. Tweetable abstract: “The study delves into the implementation of person-centred care in the Stepstones transition program for adolescents with congenital heart disease, revealing strengths and areas for improvement in documentation.”